Lembar Kerja Siswa Berbasis Budaya Lokal Ngada Untuk Pembelajaran Tematik Siswa Sekolah Dasar - Laksana, Dek Ngurah Laba; Lawe, Yosefina Uge; Ripo, Frumensia; Bolo, Maria Oliva; Dua, Tarsisius Donbosko (JURNAL PENDIDIKAN DASAR NUSANTARA, 2020)
Recent instructions has been focusing on critical thinking skills by utilizing contextual learning resources. Therefore, this study was conducted by aiming at describing the quality of local culture-based students’ worksheet from the aspect of content, instructional design, instructional media, and the product users in accordance with the characteristics of primary school students. The integrated local culture-based worksheet was developed by using ADDIE model (analyze, design, development, implementation, and evaluation). The data collected n study were analyzed descriptive qualitatively. Further, this study produced a thematic students’ worksheet on three main topics. The perception of the expert of instructional content to the integrated local-culture based worksheet was also in excellent category. On the other hand, the perception of the expert of instructional design and instructional media were in good category. Lastly, the perception of the students as the product users was in excellent category. Thus, it can be concluded that the developed worksheet has been suited to the primary school students’ characteristics.